Comparison of methods for the detection of biofilm production in coagulase-negative staphylococci - Oliveira, A. [UNESP] (2011)
Coagulase-negative staphylococci (CNS) are most often associated. with nosocomial infections, especially in premature and under weight newborns. The most important pathogenic factor of these microorganisms is the production of extracellular polysaccharide and the consequent formation of biofilm which facilitates their adherence to the surfaces of catheters and other medical devices. A total of 100 clinical samples of coagulase-negative staphylococci (CNS) isolated from infected medical devices received from the Neonatal Unit, University Hospital, Botucatu Medical Schooll, including 50 isolated from catheter tips, 30 from blood cultures, and 20 collected from the nasal cavity of healthy subjects were investigated in order to evaluate the efficiency of three phenotypic methods of detection of biofilm formation, and also analyze the icaA, icaD and icaC genes, using the PCR method. The clinical isolates were screened by Tissue Culture Plate (TCP), Borosilicate Tube Method (TM), and Congo Red Agar (CRA) method. Of the 100 tested isolates, 82% were positive in the PCR method; in the TM, 82%; in the TCP assay, 81%; and 76% in CRA method. The method of adherence to the borosilicate test tube was the method that best correlated with the detection of the ica genes, showing better sensitivity and specificity when compared with the PCR technique. Our data indicates that the Tube Method is an accurate and reproducible method for screening and this technique can serve as a reliable tool for determining biofilm formation by clinical isolates of staphylococci, once it is also a fast, easy and low-cost method.